Partial Differential Equations
Partial Differential Equations
Partial Differential Equations
SOLVED EXAMPLES
Solution
This equation is of the form Pp + Qq = R (Lagrange’s Linear equation).
Here P = xz, Q = yz and R = xy.
dx dy dz
Subsidiary equations: = =
xz yz xy
dx dy st
Grouping I: = (1 and 2nd ratios)
x y
Integrating, log x = log y + log c1 .
x
i.e., log x = log yc1 ⇒ = c1
y
dy dz nd
Grouping II: = (2 and 3rd ratios)
yz xy
⇒ xdy = zdz
⇒ yc1dy = zdz
y2 z2 x y2 z2
Integrating c1 = + c2 , = + c2
2 2 y 2 2
⇒ xy − z 2 = c2
x
Hence u= and v = xy − z 2
y
∴ The solution is f (u, v) = 0
x
i.e., f , xy − z 2 = 0.
y
Example 2 Solve px 2 + qy2 = z 2 . (AU. NOV./DEC. 2005)
Solution
This equation is Lagrange’s Linear equation Pp + Qq = R
where P = x 2 , Q = y 2 and R = z 2
dx dy dz
Subsidiary equations: = = (1)
x 2 y2 z2
dx dy
Grouping I: From (1), consider first and second ratios =
x 2 y2
1 1 1 1
Integrating we get − = − + c1 ⇒ − = c1
x y y x
dy dz
Grouping II: From (1), taking 2nd and 3rd ratios, =
y2 z2
1 1
Integrating, we get − = c2
z y
1 1 1 1
∴ The solution is f − , − = 0.
y x z y
Example 3 Solve qy − px = z.
Solution
y
∴ = c2
z
y
∴ The solution is f xy, = 0.
z
y2 z
Example 4 Solve y2 zp + x 2 zq = y2 x (or) p + xzq = y2 .
x
Solution
The given equation is Lagrange’s Linear equation Pp + Qq = R
Here P = y 2 z; Q = x 2 z and R = y 2 x
dx dy dz
Subsidiary Equations: 2
= 2 = 2 (1)
y z x z y x
dx dy
Grouping I: From (1), consider 1st and 2nd ratios 2
= 2
y z x z
⇒ x 2 dx = y 2 dy
x 3 y3
Integrating, we get = + c1 ⇒ x 3 − y 3 = c1
3 3
dx dz
Grouping II: From (1), consider first and last ratios, 2
= 2
y z y x
⇒ xdx − zdz = 0
Solution
This is Lagrange’s Linear equation Pp + Qq + R
Here p = y 2 ; Q = − yx and R = x( z − 2 y)
dx dy dz
Subsidiary equations: = = (1)
y 2
− yx x( z − 2 y)
dx dy
Grouping I: From (1), consider 1st and 2nd ratios, =
y 2
− yx
⇒ xdx + ydy = 0; xdx + ydy = 0
x 2 y2
Integrating, we get + = c1
2 2
⇒ x 2 + y 2 = c1
dy dz
Grouping II: − =
xy x( z − 2 y)
⇒ ( z − 2 y)dy + ydz = 0
∴ ydz + zdy − 2 ydy = 0
i.e., d ( yz ) − 2 ydy = 0
Integrating, yz − y 2 = c2
∴ The solution is f ( x 2 + y 2 , yz − y 2 ) = 0.
Example 6 Solve pz − qz = z 2 + ( x + y)2 .
Solution
This is Lagrange’s Linear equation Pp + Qq = R
where P = z; Q = − z and R = z 2 + ( x + y)2
dx dy dz
Subsidiary equations: = = 2 (1)
z − z z + ( x + y )2
dx dy
Grouping I: From (1), first and second ratios give =−
z z
⇒ dx + dy = 0 Integrating, x + y = c1
Grouping II: From (1), consider 1st and 3rd ratios
dx dz
= 2 C
z z + ( x + y )2
dx dx
⇒ = 2
z z + c12
zdz
∴ dx =
z + c12
2
1
Integrating, x + c2 = log z 2 + ( x + y)2
2
⇒ c2 = log z 2 + ( x + y)2 − 2 x
Solution
The given equation is of the form Pp + Qq = R (Lagrange’s Linear equation)
Here P = y − z; Q = z − x; R = x − y
dx dy dz
Subsidiary Equations: = =
y−z z−x x−y
Choosing multipliers (l, m, n) = (1, 1, 1),
dx dy dz dx + dy + dz dx + dy + dz
= = = =
y−z z−x x−y y−z+z−x+x−y 0
⇒ dx + dy + dz = 0
Integrating, we get x + y + z = c1
l ′P + m ’Q + n ′R = xy − xz + yz − xy + xz − yz = 0
∴ l ′dx + m ′dy + n ′dz = 0
⇒ xdx + ydy + zdz = 0
x 2 y2 z2
Integrating + + = constant
2 2 2
∴ x 2 + y 2 + z 2 = c2
Hence the solutions is f [ x + y + z, x 2 + y 2 + z 2 ] = 0.
Solution
The given equation is Lagrange’s Linear equation Pp + Qq = R
Here P = y + z; Q = − x − z and R = x − y
dx dy dz
Subsidiary equations: = = (1)
y + z −x − z x − y
We choose set of multipliers (l, m, n) = (1, 1, 1)
Pp + mQ + nR = y + z − z − x + x − y = 0
⇒ ldx + mdy + ndz = 0 ⇒ dx + dy + dz = 0
Integrating x + y + z = c1
∴ u= x+ y+z
We choose another set of multipliers (l ′, m ′, n ′ ) = ( x, y, − z )
l ′P + m ′Q + n ′R = x( y + z ) − y( x + z ) − z( x − y)
= xy + xz − xy − yz − xz + yz = 0
⇒ l ′dx + m ′dy + n ′dz = 0
i.e., xdx + ydy − zdz = 0
Integrating x 2 + y 2 − z 2 = c2
⇒ v = x 2 + y2 − z2
∴ The solution is f ( x + y + z. x 2 + y 2 − z 2 ) = 0.
Example 9 Solve x 2 ( y − z ) p + y2 ( z − x )q = z 2 ( x − y).
Solution
The given equation is Lagrange’s Linear equation Pp + Qq = R
Here P = x 2 ( y − z ); Q = y 2 ( z − x ) and R = z 2 ( x − y)
dx dy dz
Subsidiary equations: = 2 = 2 (1)
x ( y − z ) y ( z − x ) z ( x − y)
2
1 1 1
In (1), we use the multipliers (l, m, n) = 2 , 2 , 2
x y z
lP + mQ + nR = y − z + z − x + x − y = 0
∴ ldx + mdy + ndz = 0
dx dy dz
⇒ + + =0
x 2 y2 z2
1 1 1
Integrating, − − − = constant
x y z
1 1 1
⇒ + + = c1
x y z
1 1 1
In (1), using multipliers (l ′, m ′, n ′ ) = , , ,
x y z
We have l ′P + m ′Q + n ′R = xy − xz + yz − xy + zx − yz = 0
⇒ l ′dx + m ′dy + n ′dz = 0
dx dy dz
∴ + + =0
x y z
Integrating, log x + log y + log z = log c2
⇒ log( xyz ) = log c2
⇒ xyz = c2
1 1 1
∴ The solution is f + + , xyz = 0.
x y z
∂z ∂z
Example 10 Solve ( mz − ny) + ( nx − lz ) = ly − mx.
∂x ∂y (AU. APR./MAY 2004)
Solution
The given equation is Pp + Qq = R
dx dy dz
Subsidiary equation: = =
mz − ny nz − lz ly − mx
Using multipliers (l, m, n) = ( x, y, z )
xdy + ydy + zdz
We get each fraction =
0
∴ xdx + ydy + zdz = 0
Integrating, x 2 + y 2 + z 2 = c1
Again using multipliers (l ′, m ’, n ′ ) = (l, m, n)
ldx + mdy + ndz
We get each fraction =
0
∴ ldx + mdy + ndz = 0
Integrating, lx + my + nz = c2
∴ The required solution is f x 2 + y 2 + z 2 , lx + my + nz = 0.
Solution
The given equation is p( y − xz ) + ( yz − x )q = ( x + y)( x − y)
dx dy dz
The A.E. is = = 2 (1)
y − xz yz − x x − y 2
Using multipliers x, y, z in (1), each ratio
xdx + ydy + zdz xdx + ydy + zdz
= =
xy − x z + y z − yx + x z − y z
2 2 2 2
0
⇒ xdx + ydy + zdz = 0
Integrating, x 2 + y 2 + z 2 = c1
Using multipliers y, x, 1 in (1), we get ydx + xdy + dx = 0
⇒ d ( xy) + dx = 0
Integrating, xy + z = c2
∴ The general solution is f ( xy + z, x 2 + y 2 + z 2 ) = 0
or xy + z = f ( x 2 + y 2 + z 2 ).
Example 12 Solve ( x 2 − yz ) p + ( y2 − zx )q = z 2 − xy. (AU. MAY 1996)
Solution
The equation is of the form Pp + Qq = R
Here P = x 2 − yz; Q = y 2 − zx; R = z 2 − xy
1
P.I 2 = sin(3 x + 2 y)
D − 3 DD ′ + 2 D ′ 2
2
∂2 z ∂2 z ∂2 z
Example 2 Solve −4 + 4 2 = e2 x+ y . (AU. MAY/JUNE 2006)
∂x 2
∂x∂y ∂y
Solution
Symbolic form ( D 2 − 4 DD ′ + 4 D ′ 2 )z = e2 x + y
∂ ∂
Where D = and D ′ =
∂x ∂y
The auxiliary equation is m 2 − 4 m + 4 = 0
i.e., (m − 2)2 = 0 ⇒ m = 2, 2
∴ C.F = f1 ( y + 2 x ) + xf2 ( y + 2 x )
1
P.I = e2 x + y
( D − 2 D ′) 2
1
Put D = 2 and D ′ = 1, the denominator vanishes. e2 x + y = xe2 x + y
D − 2D′
xe2 x + y
∴ P.I = [Differentiate ( D − 2 D ′ ) W.r.to D]
2
2( D − 2 D ′ )
x2 2 x+ y
=
e , since Dr=0 for D = 2, & D ′ = 1
2
x2
∴ The general solution is z = f1 ( y + 2 x ) + xf2 ( y + 2 x ) + e2 x + y .
2
Solution
The auxiliary equation is m 2 + 4 m − 5 = 0
i.e., (m + 5)(m − 1) = 0
∴ m = −5, 1
C .F = f ( y + 2 x ) + g( y − 5 x )
1
P.I1 = 2 3e2 x − y
D + 4 DD ′ − 5 D ′ 2
Put D = 2, D ′ = −1
1
P.I1 = − e2 x − y
3
1
P.I 2 = sin( x − 2 y)
D + 4 DD ′ − 5 D ′ 2
2
Put D 2 = −1, DD ′ = 2, D ′ 2 = −4
1
P.I 2 = sin( x − 2 y)
27
e2 x − y 1
∴ The solution is z = f ( y + x ) + g( y − 5 x ) + + sin( x − 2 y).
3 27
Example 4 Solve ( D 2 + 3 DD ′ − 4 D ′ 2 ) z = cos( 2 x + y) + xy.
Solution
The auxiliary equation is m 2 + 3m − 4 = 0
∴ (m + 4)(m − 1) = 0 ⇒ m = −4, 1
C.F = f1 ( y − 4 x ) + f2 ( y + x )
1
P. I 1 = 2 cos(2 x + y)
D + 3 DD ′ − 4 D ′ 2
Put D 2 = −4, DD ′ = −2, D ′ 2 = −1
1 cos(2 x + y)
∴ P.I1 = cos(2 x + y) = −
−4 − 6 + 4 6
1 1
P.I 2 = xy = xy
D 2 + 3 DD ′ − 4 D ′ 2 3D ′ 4 D ′ 2
D 1 +
2
− 2
D D
1 3D ′ D′2
= 2 (1 + u)−1 xy where u = −4 2
D D D
1
= 2 [1 − u + u 2 − ...]xy
D
1 3D ′ 4 D ′ 2 1 3
= 2 1 − + 2
+ ... xy = 2 xy − ( x )
D D D D D
54. Solve p2 − x = q 2 − y.
Solution
p 2 − x = q 2 − y = a (say) ∴ p = a + x and q = a + y
2
∴ z = (a + x )3 / 2 + 2 / 3(a + y)3 / 2 + b is the complete integral.
3
∂2 z ∂2 z ∂2 z
55. Solve + + 4 2 = 0.
∂x 2
∂x∂y ∂y
Solution
Auxiliary equation is m 2 − 4 m + 4 = 0 (m − 2)2 = 0 ⇒ m = 2, 2
∴ The general solution is z = f 1 ( y + 2 x ) + xf 2 ( y + 2 x ).
56. Solve ( D 2 + 3 DD ′ + 2 D ′ 2 ) z = 0.
Solution
Auxiliary equation is m 2 + 3m + 2 = 0 i.e., (m + 1)(m + 2) = 0
∴ m = −1, −2 ∴ The solution is z = f1 ( y − x ) + f2 ( y − 2 x ).
57. Solve ( D 3 − 7 DD ′ 2 − 6 D ′ 3 ) z = 0.
Solution
The auxiliary equation is m 3 − 7m − 6 ⇒ (m + 1)(m 2 − m − 6) = 0
∴ (m + 1)(m − 3)(m + 2) = 0 ∴ m = −2, −1, 3
∴ The solution is z = f1 ( y − 2 x ) + f2 ( y − x ) + f3 ( y + 3 x ).
58. Solve ( D 2 + 2 DD ′ + D ′ 2 ) z = 0.
Solution
The auxiliary equation is m 2 + 2 m + 1 = 0 i.e.,(m + 1)2 = 0
∴ m = −1, −1. ∴ The solution is z = f1 ( y − x ) + xf2 ( y − x ).
∂2 z ∂2 z ∂2 z
59. Find the general solution of − 6 + 5 = 0.
∂x 2 ∂x∂y ∂y2
Solution
Auxiliary equation is m 2 − 6 m + 5 = 0 i.e., (m − 5)(m − 1) = 0
∴ m = 1, 5 The solution is z = f1 ( y + x ) + f2 ( y + 5 x ).
∂2 z ∂2 z
60. Find the Particular integral of − = sin( x − y).
∂x 2 ∂x∂y
Solution
1
P. I = sin( x − y) Put D 2 = −1, DD ′ = −(1) ( −1) = 1
D 2 − DD ′
1 − sin( x − y)
∴ P.I = sin( x − y) = .
−1 − 1 2
61. Find the particular integral of ( D 2 − 4 DD ′ + 3 D ′ 2 ) z = e x + y .
Solution
1
P.I = e x + y Put D = 1, D′ = 1.
D − 4 DD ′ + 3 D ′ 2
2
x xe x + y
Denominator = 0 ∴ P.I = ex+ y = − .
2D − 4D′ 2
Solution
1
P.I = ex−y
D + 3 DD ′ + 4 D ′ 2
2
1 ex−y
Put D = 1, D ′ = −1 = ex−y = .
1− 3+ 4 2
63. Solve ( D 2 − 2 DD ′ + D ′ 2 ) z = 0.
Solution
Auxiliary equation is m 2 − 2 m + 1 = 0 i.e., (m − 1)2 = 0 ⇒ m = +1,1
The general solution is z = f1 ( y + x ) + xf2 ( y + x ).
∂2 z ∂2 z ∂2 z
64. Find the particular integral of − 3 + 2 = sin( x − 2 y).
∂x 2 ∂x∂y ∂y2
Solution
1
P.I = sin( x − 2 y) put D 2 = −1, DD ′ = 2, D ′ 2 = −4
D − 3 DD ′ + 2 D ′
2 2
1 − sin ( x − 2 y)
∴ P.I = sin( x − 2 y) = .
−1 − 6 − 8 15
Solution
1 1 D′ 2
P.I = x2 y = 1 + D ( x y)
D′ 6 D′ 2
D2
D 2 1 − − 2
D D
1 2 x3 x 4 y x5
= x y + = + .
D2 3 12 60
Solution
1
P.I = e2 x − y Put D = 2 D′ = -1
( D − 2 D ′) 2
1 e2 x − y
Then P.I = e2 x − y = .
(2 + 2 ) 2
16
Solution
1
P.I = cos 2 x cos 3 y
D − 4D′2
2
1 cos 2 x cos 3 y
= cos 2 x cos 3 y = .
−4 − ( −36) 32
68. Solve ( D 2 − 4 DD ′ + 5 D ′ 2 ) z = 0.
Solution
The Auxiliary equation is m2 – 4m + 5 = 0
4 ± 16 − 20
⇒ m= = 2 ± i ∴ m1 = 2 + i & m2 = 2 − i
2
The complete solution is z = f1 ( y + m1 x ) + f 2 ( y + m2 x )
where m1 = 2 + i and m2 = 2 – i.
69. Solve ( D 2 − D ′ 2 − 3 D + 3 D ′ ) z = 0.
Solution
[( D − D ′)( D + D ′) − 3( D − D ′)] z = 0
i.e., ( D − D ′ )( D + D ′ − 3)z = 0 ( D − D ′ )z = 0 ⇒ z = f 1 ( y + x )
( D + D ′ − 3) = 0 z = e3 xf 2 ( y − x )
Solution
1 2 D′ 2
2
1 2 x4
P.I = 1 + C x = ( x ) = .
D2 D 2 D2 12
∂z ∂z
71. Find the complete integral of p + q = pq where p = and q = .
∂x ∂x
Solution
The equation is f ( p, q ) = 0.
The complete integral is z = ax + by + c where a and b are connected by
a
f (a, b) = 0 ⇒ a + b = ab ∴ b =
a −1
ay
The complete integral is z = ax + + C.
a −1
∂u ∂u
Example 2 Using the method of separation of variables, solve =2 +u
∂x ∂t
where u ( x,0 ) = 6 e −3 x
Solution
Let u = X ( x ) T (t ) be the solution
∂u ∂u
Then = X ′T and = XT ′
∂x ∂t
Substituting these in the given equation, X ′T = 2 XT ′ + XT
( X ′ − X ) T = 2 XT ′
X′ − X T ′
= = k (say)
\ 2X T
⇒ X ′ − X = 2 Xk and T ′ = kT
\ X ′ = (2 k + 1) X and T ′ = kT
X′
= (2 k + 1) gives X = c1e( + k ) x and
1 2
Solving
X
T′
Solving =k gives T = c2 e kt
T
\ The solution is u = X ( x ) T (t )
u = Ae( )
1+ 2 k x + kt
⇒
Using u ( x,0 ) = 6e −3 x in (1), A = 6 and 1 + 2 k = −3
\ A = 6, k = −2
− (3 x + 2 t )
Hence the solution is u = 6e .
∂u ∂u
Example 3 Solve the equations 3 +2 = 0, given that u ( x,0 ) = 4e − x by
∂x ∂y
the method of separation of variables. [AU. NOV. 2007]
Solution
Let u ( x,y ) = X ( x )Y ( y )
Then ux = X 1Y and uy = XY 1
3 x1 2Y 1
\ 3 X 1 y + 2 XY 1 = 0 ⇒ + =0
X Y
3X ′ 2Y ′ 3X ′ X′ k
\ =− =k = k⇒ =
X Y X X 3
k
Integrating, log X = X + log c1
3
kx
\ X = c1e 3
2Y ′ Y′ k
− =k⇒ =− ,
Y Y 2
− ky
Integrating Y = c2 e 2
x
k − y
\ u = ce 3 2
u = ( x,0 ) = ce
k x
Given 3
= 4 e− x
⇒ c = 4 and k = −3
− x +3 y
Hence the solution is u ( x,y ) = 4e 2
.
kx + ky ky
\ u ( x,y ) = ce 4
u (o,y ) = ce 4
∂u ∂u
Example 5 Use the separation of variables technique to solve 3. + 2. =0
∂x ∂y
with u ( x, 0 ) = 4 e − x .
Solution
Assume u ( x, y ) = X ( x )Y ( y )
\ u = XY
Then P.D.E becomes 3 X ′Y + 2 XY ′ = 0
X ′ −2 Y ′
⇒ = = k = constant
X 3 Y
Y ′ −3
\ X ′ − kX = 0 and = k
Y 2
3
ky
Solving X = c1e kx and Y = c2 e 2
3
kx − ky
\ u = c.e 2
k
(2 x − 3 y )
u ( x, y ) = ce 2
Given u ( x,0 ) = 4e − x
From(1), ce kx = 4e − x ⇒ c = 4 and k = −1
1
(2 x − 3 y )
\ u ( x, y ) = 4e 2
Solution
Assume u(x,y) = X ( x )Y ( y )
Dividing by XY,
X′ Y ′
4 + =3
X Y
X′ Y′
∴ 4 =3− = k ( say )
X Y
X′ k Y′
⇒ = and = 3 − k
X 4 Y
X′ k kx
= ⇒ X = c1e 4
X 4
Y′
= 3 − k ⇒ Y = c2 e( )
3− k y
Y
x
k − y
\ u = ce 4
⋅ e3 y
x
k − y
u ( x, y ) = ce3 y e 4
Solution
Assume u ( x, y ) = X ( x )Y ( y )
\ X ′Y = 4 XY ′
X ′ 4Y ′
⇒ = = k (say)
X Y
X′
= k ⇒ X ( x ) = c1e kx
X
4Y ′ ky
= k ⇒ Y ( y ) = c2 e 4
Y
ky
\ u ( x, y ) = ce kx ⋅ e 4
y
k x−
4
= ce
ky
u (0, y ) = 8e −3 y ⇒ ce 4
= 8e −3 y
∴ c = 8 and k = − 12
\ The solution is u ( x, y ) = 8e −12 x − 3 y .
EXERCISES
ANSWERS
1. u = 4e −3 x − 2 t 2. z = e2 x − 5 y 3. u = 4e x − y − e2 x − 5 y
Example
Elliptic type (i) uxx + uyy = 0 (Laplace Equation)